Synthesis and Optical Studies of the 3,4-dimethoxy Benzaldehyde [5-(2-hydroxyphenyl)-1,3,4-oxadiazol-2-yl]Hydrazone Metal Complexes - Athraa H. Mekkey; Fatima H. Mal; Samah H. Kadhim (University of Thi-Qar Journal of Science, 2020)
The aim of the present study is to synthesize and optical studies of 3,4-dimethoxy benzaldehyde [5-(2-hydroxyphenyl)-1,3,4-oxadiazol-2-yl]hydrazone metal complexes. Firstly, the 3,4-dimethoxybenzaldehyde [5-(2-hydroxyphenyl)-1,3,4-oxadiazol-2-yl] hydra zone was synthesized by the reaction of the 2-(5-hydrazino-1,3,4-oxadiazol-2-yl)phenol with 2,3-dimethoxybenzaldehyde in the ethanol as a solvent . Scondly, its complexes of Cr(III), Fe(III), Co(II) and Ni (II) have been synthesized. The synthesized coumpounds and its metal complexes were characterized by the FTIR, Mass spectra and UV-vis absorption. The results confirmed the suggested square planar geometry of the Ni (II) complex and tetrahedral geometry of the Co(II) complex, while Cr (III), Fe(III) complexes were assigned octahedral geometrics. The optical absorption spectra of those complexes in the wavelength range from 200-900 nm were studied.The results showed that the optical absorption is due to indirect allowed transitions of the compound and its complexes, the energy gap (Eg) of these compounds decreases in the order L> Ni (II)> Fe(III)> Co(II) and > Cr(III), the absorption coefficient (α), real and imaginary parts (ɛr,ɛi), and optical conductivity (σopt)were estimated.